Quality of Cattle Meat and Its Compositional Constituents - Umer Seid Geletu; Munera Ahmednur Usmael; Yesihak Yusuf Mummed; Abdulmuen Mohammed Ibrahim (Veterinary Medicine International)
Meat is the most valuable livestock product since it is one of the main sources of protein for human consumption. Meat quality can be evaluated according to the following parameters: pH, amount of lactic acid, volatile fatty acids, bounded water, solubility of proteins, color, and tenderness. The meat composition and physical properties of muscles have been characterized for ensuring improved eating quality. Thus, the purpose of this paper was to review the major chemical compositional and physicochemical properties of meat and, at the same time, its quality attributes and factors that affect quality of meat. A number of structural features of meat as connective tissue, muscle fibers, and tendon that attaches the muscle to the bone are visible in joint meat examined through naked eyes. Water is quantitatively the most important component of meat comprising up to 75% of weight. Meat is also composed of amino acids, fatty acids, vitamins, minerals, and other important ingredients. Quality factors perceived by consumers are related to sensory attributes (e.g., color, tenderness, and flavor), nutritional properties (e.g., calories, vitamins’ content, and fatty acids’ profile), and appearance (e.g., exudation, marbling, and visible amount of fat). However, fresh meat quality can be defined instrumentally including composition, nutrients, color, water-holding capacity, tenderness, functionality, flavors, spoilage, and contamination. Visual inspection based on sensory quality attributes and different chemical methods are used to analyze meat quality. Other methods such as computer vision and imaging spectroscopy, gas chromatographic analysis, near-infrared technology, dual-energy X-ray absorptiometry, and computerized tomography scanning are also used in the meat industry. So, the aim of the present review is to review quality characteristics of cattle meat and its composition constituents.